Roman law and common law : a comparison in outline / by W.W.Buckland and A.D. McNair. 2nd ed. rev. by F.H.Lawson - Buckland, W.W. ; McNair, A.D. ; Lawson, F.H. (Cambridge University Press, 1952)
xx, 439 halaman ; 22 cm